2008
DOI: 10.1159/000139579
|View full text |Cite
|
Sign up to set email alerts
|

NELL2, a Neuron-Specific EGF-Like Protein, Is Selectively Expressed in Glutamatergic Neurons and Contributes to the Glutamatergic Control of GnRH Neurons at Puberty

Abstract: NELL2, a protein containing EGF-like repeats, is almost exclusively expressed in the nervous system. In the mammalian brain, NELL2 expression is mostly neuronal. NELL2 was previously found to be a secreted protein that functions during embryonic development as a neuronal differentiation and survival factor. We now show that the Nell2 gene is selectively expressed in the two major subtypes of glutamatergic neurons described in the postnatal brain: those containing the vesicular glutamate transporter 1 and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 80 publications
2
53
2
Order By: Relevance
“…We also identified that NELL2 is specifically expressed in hypothalamic cells expressing ERα and is involved in E2-dependent hypothalamic sexual differentiation (Jeong et al, 2008a) and reproductive maturation (Ha et al, 2008), while GnRH neurons do not express ERα, a major feedback regulator for the GnRH neural apparatus (Herbison and Theodosis, 1992). Therefore, NELL2 might be essential to the E2-dependent control of neuroendocrine events related to reproduction, such as puberty initiation (Ha et al, 2008) and female reproductive cyclicity.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…We also identified that NELL2 is specifically expressed in hypothalamic cells expressing ERα and is involved in E2-dependent hypothalamic sexual differentiation (Jeong et al, 2008a) and reproductive maturation (Ha et al, 2008), while GnRH neurons do not express ERα, a major feedback regulator for the GnRH neural apparatus (Herbison and Theodosis, 1992). Therefore, NELL2 might be essential to the E2-dependent control of neuroendocrine events related to reproduction, such as puberty initiation (Ha et al, 2008) and female reproductive cyclicity.…”
Section: Introductionmentioning
confidence: 91%
“…Proteins on the gel were transferred onto a nitrocellulose membrane (Amersham Biosciences, UK) by an electrophoretic transfer cell (Bio-Rad Laboratories, USA). The membrane was incubated with primary antibody (rabbit anti-NELL2, 1:1000) (Ha et al, 2008) for 1 h in hybridization buffer (1x Tris-buffered saline with 0.1% Tween 20, 1% milk) and followed by incubation with secondary antibody (anti-rabbit IgG, 1:2000; Amersham Biosciences). The immunoreactions were detected with an enhanced chemiluminescence detection kit (Amersham Biosciences) according to the supplied protocol.…”
Section: Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybridization was performed using anti-green fluorescent protein (GFP) antibody [Santa Cruz Biotechnology Inc. (Germany), 1:1000] and anti-NELL2 antibody (1:500, see Ha et al, 2008 for the generation and verification of the antibody). The epitope of the anti-NELL2 antibody is amino acids 273-588 of the rat NELL2 protein.…”
Section: Western Blottingmentioning
confidence: 99%